Treatment of covert food stealing in an individual with Prader-Willi syndrome. - Maglieri, K A (2000)
Covert food stealing is common among individuals with Prader-Willi syndrome. We found that verbal reprimands, delivered contingent upon eating prohibited foods, were sufficient to decrease the food stealing of a girl with Prader-Willi syndrome. Warning stimuli were then used to help her discriminate between permitted and prohibited foods during sessions in which food stealing was not directly observed. This procedure resulted in decreases in food stealing from containers labeled with the warning stimuli.